Evaluasi Penyajian Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Keuangan Entitas Tanpa Akuntabilitas Publik Pada Perusahaan Daerah Air Minum Kabupaten Maluku Tenggara - Regina Redemta Ohoiwai; Andrew Marunduh; Pricilia Joice Pesak (Fakultas Ekonomi Universitas Negeri Manado, 2022)
The purpose of this research is to evaluate the presentation of financial statements based on the Financial Accounting Standards of Entities Without Public Accountability at the Regional Water Company of Southeast Maluku Regency. The method used in this research is descriptive research with a qualitative approach. The results of this study are that the Southeast Maluku Regency PDAM has presented financial statements in the form of balance sheets, profit/loss reports, reports of changes in equity, cash flow statements, and notes to financial statements. However, the balance sheet and profit/loss report are not fully in accordance with SAK ETAP because PDAM Kabupaten Maluku Tenggara does not include several posts or items in it, while the statement of changes in equity, cash flow statement and notes to financial statements are in accordance with SAK-ETAP.